2009
DOI: 10.1038/eye.2008.394
|View full text |Cite
|
Sign up to set email alerts
|

Routine, single session, indirect laser for proliferative diabetic retinopathy

Abstract: Aims To evaluate the visual and morphological outcomes of routine, single session, indirect panretinal photocoagulation (PRP) for proliferative diabetic retinopathy, and to examine adverse events related to indirect laser within the first 8 weeks of treatment. Methods The case notes of 107 diabetics with proliferative retinopathy undergoing indirect PRP were reviewed retrospectively, and compared with the UK National Diabetic Retinopathy Laser Treatment Audit. Patients who had received PRP previously were excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…In the present study Panretinal photocoagulation is well tolerated by the patients, without interfering significantly with their quality of life in accordance with the study made by Tsilimbaris MK et al all studied on 20 patients with bilateral proliferative diabetic retinopathy treated with panretinal photocoagulation his study revealed that Panretinal photocoagulation although destructive in nature, is well tolerated by the patients, without interfering significantly with their quality of life 11 PRP significantly reduces the risk of severe vision loss in PDR patients by 50% in accordance with the study done by ETDRS and DRS control trials. In our study also, 80 eyes who underwent PRP visual acuity improved in 21.1%, visual acuity was maintained in 70.6% and decreased in 8.2% which was more than the ETDRS and DRS studies.…”
Section: Discussionsupporting
confidence: 74%
“…In the present study Panretinal photocoagulation is well tolerated by the patients, without interfering significantly with their quality of life in accordance with the study made by Tsilimbaris MK et al all studied on 20 patients with bilateral proliferative diabetic retinopathy treated with panretinal photocoagulation his study revealed that Panretinal photocoagulation although destructive in nature, is well tolerated by the patients, without interfering significantly with their quality of life 11 PRP significantly reduces the risk of severe vision loss in PDR patients by 50% in accordance with the study done by ETDRS and DRS control trials. In our study also, 80 eyes who underwent PRP visual acuity improved in 21.1%, visual acuity was maintained in 70.6% and decreased in 8.2% which was more than the ETDRS and DRS studies.…”
Section: Discussionsupporting
confidence: 74%
“…In our study was 10% recurrence was noted in patients treated with photocoagulation. Other author also found the good results by photocoagulation [7,11,12,13]. In this study there were 10 cases where vitreous haemorrhage persisted for 6 month.…”
Section: Discussionsupporting
confidence: 64%
“…The early rabbit OCT shows shallow exudative retinal detachment, which we have also observed in rabbit histology (not shown), but not in patient OCT. Here, overtreatment would rather cause choroidal effusion (Tinley & Gray 2009). Figure 4 shows linear regression analyses of ophthalmoscopical lesion diameters and OCT or histological GLD's, respectively.…”
Section: Detailed Qualitative Lesion Correlation With Different Intenmentioning
confidence: 99%